ChemInform Abstract: A Z‐Scheme Visible‐Light‐Driven Ag/Ag3PO4/Bi2MoO6 Photocatalyst: Synthesis and Enhanced Photocatalytic Activity. Issue 11 (February 2016) - Lin, Xue; Hou, Jing; Jiang, Shanshan; Lin, Zhe; Wang, Miao; Che, Guangbo
Abstract: A Ag/Ag3 PO4 /Bi2 MoO6 composite is prepared via in situ precipitation using an aqueous Bi2 MoO6 nanosheet dispersion to which aqueous solutions of AgNO3 and Na3 PO4 are given in succession.